La représentation du Brésil et de ses habitants dans l’Europe de la fin du xvie siècle - Grégory Wallerick (Confins)
At the end of the 16th century, the protestant engraver Theodor de Bry illustrated two travels to a part of America: Brazil. In this country, Europeans met a tribe who used to eat humans during a ritual ceremony. With the third part of the Grands Voyages, European people considered that Brazil and his inhabitants looked like cards and pictures in this book. The representation of this country kept for a few centuries, and at the independence of Brazil, some cards of De Bry were used to determine the limits of the new state.